Analysis of out-of-pocket health expenditure using the WHO Global Health Expenditure Database (GHED): A systematic review - González R, Dr. Marino J (Gaceta Médica de Caracas, 2020)
Tracking out-of-pocket (OOP) health expenditure is a very useful reference for knowing the progress of countries in the goal of universal health coverage (UHC) in 2030. The World Health Organization (WHO) has developed the Global Health Expenditure Database (GHED) to facilitate analysis of health financing in countries or regions. The paper explores the use of GHED in the analysis of OOP health expenditure in the specialized literature. El seguimiento del gasto de bolsillo (OOP) en salud es una referencia muy útil para conocer el progreso de los países en el objetivo de la cobertura universal de salud (CSU) en 2030. La Organización Mundial de la Salud (OMS) ha desarrollado la Base de Datos de Gasto en Salud Global (GHED) para facilitar el análisis del financiamiento de la salud en países o regiones. El artículo explora el uso de GHED en el análisis del gasto en salud OOP en la literatura especializada.